PLC-controlled stepper motor drive for NC positioning system - Sarhan, Hussein (International Journal of Engineering and Technology, 2014)
In this paper, an electric drive system for precision control of numerically-controlled positioning system is designed, assembled and experimentally tested. The proposed drive system is based on PLC-controlled stepper motor. The PLC is used as an indexer to perform full stepping, half stepping and microstepping modes of operation of stepper motor. The drive system has been implemented in two-axes NC positioning system. The linear displacement for each machine axis has been evaluated and compared for the three stepping modes of stepper motor. Experimental and calculation results show that the response per pulse (resolution) for full stepping mode is , for half stepping mode is and for microstepping mode is , which means that the microstepping mode is the best one for precision control of NC positioning system. Keywords: Electric Drive, NC Positioning System, PLC, Stepper Motor, Stepping Mode.